A common language to assess allergic rhinitis control: results from a survey conducted during EAACI 2013 Congress. Issue 1 (December 2015) - Hellings, Peter; Muraro, Antonella; Fokkens, Wytske; Mullol, Joaquim; Bachert, Claus; Canonica, G.; Price, David; Papadopoulos, Nikos; Scadding, Glenis; Rasp, Gerd; Demoly, Pascal; Murray, Ruth; et al.
Abstract Background The concept of control is gaining importance in the field of allergic rhinitis (AR), with a visual analogue scale (VAS) score being a validated, easy and attractive tool to evaluate AR symptom control. The doctors' perception of a VAS score as a good tool for evaluating AR symptom control is unknown, as is the level of AR control perceived by physicians who treat patients. Methods 307 voluntarily selected physicians attending the annual (2013) European Academy of Allergy and Clinical Immunology (EAACI) meeting completed a digital survey. Delegates were asked to (1) estimate how many AR patients/week they saw during the season, (2) estimate the proportion of patients they considered to have well-, partly- and un-controlled AR, (3) communicate how they gauged this control and (4) assess how useful they would find a VAS as a method of gauging control. 257 questionnaires were filled out completely and analysed. Results EAACI delegates reported seeing 46.8 [standard deviation (SD) 68.5] AR patients/week during the season. They estimated that 38.7 % (SD 24.0), 34.2 % (SD 20.2) and 20.0 % (SD 16.34) of their AR patients had well-controlled (no AR symptoms), partly-controlled (some AR symptoms), or un-controlled-(moderate/severe AR symptoms) disease despite taking medication [remainder unknown (7.1 %)]. However, AR control was assessed in many ways, including symptom severity (74 %), frequency of day- and night-time symptoms (67 %), activity impairment (57 %), respiratory function monitoring (nasal and/or lung function; 40 %) and incidence of AR exacerbations (50 %). 91 % of delegates felt a simple VAS would be a useful tool to gauge AR symptom control. Conclusions A substantial portion of patients with AR are perceived as having uncontrolled or partly controlled disease even when treated. A simple VAS score is considered a useful tool to monitor AR control.